2015
DOI: 10.1136/bmj.h3646
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative protective mechanical ventilation and risk of postoperative respiratory complications: hospital based registry study

Abstract: ObjeCtiveTo evaluate the effects of intraoperative protective ventilation on major postoperative respiratory complications and to define safe intraoperative mechanical ventilator settings that do not translate into an increased risk of postoperative respiratory complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
232
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 241 publications
(269 citation statements)
references
References 40 publications
14
232
0
14
Order By: Relevance
“…We used patient data from all sources to form one de-identified database, as previously reported by our group. [23][24][25] Patient involvement No patients were involved in setting the research question or the outcome measures, nor were they involved in developing plans for recruitment, design, or implementation of the study. No patients were asked advice on interpretation or writing up of results.…”
Section: Methods Study Populationmentioning
confidence: 99%
“…We used patient data from all sources to form one de-identified database, as previously reported by our group. [23][24][25] Patient involvement No patients were involved in setting the research question or the outcome measures, nor were they involved in developing plans for recruitment, design, or implementation of the study. No patients were asked advice on interpretation or writing up of results.…”
Section: Methods Study Populationmentioning
confidence: 99%
“…Severgnini et al 36 compared the use of a traditional ventilation strategy (V T ϭ 9 mL/kg PBW and no PEEP) with a lung-protective strategy (V T ϭ 7 mL/kg PBW with PEEP ϭ 10 cm H 2 O and recruitment maneuvers) in 56 subjects scheduled to undergo elective open abdominal surgery lasting Ͼ2 h and found that subjects in the lung-protective group had better pulmonary function tests up to day 5, fewer alterations in chest radiographs up to day 3, better oxygenation, and a lower clinical pulmonary infection score. Ladha et al 37 performed a large (69,265 subjects) hospital-based registry study in 3 Massachusetts hospitals from January 2007 to August 2014. They compared subjects who received protective mechanical ventilation (V T Ͻ10 mL/kg PBW, PEEP Ն5 cm H 2 O, and plateau pressure Ͻ30 cm H 2 O) with subjects who received non-protective mechanical ventilation in terms of postoperative respiratory complications during non-cardiac surgery.…”
Section: Ventilation Of Surgical Patientsmentioning
confidence: 99%
“…1113 Recent studies have reported contradictory results regarding the association between PEEP and the risk of postoperative respiratory complications. 1417 …”
mentioning
confidence: 99%